The Influence of Leadership Styles and Work Motivation on Teacher’s Performance - Astuti, Retno Widia; Fitria, Happy; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2020)
This study determined the influence of the principal's leadership style and work motivation on the performance of high school teachers. Data in this study were collected through distributing the questionnaires to respondents. The results of the questionnaire were analyzed by using multiple regression analysis through t-test, F-test, and the coefficient of determination. Population in this study was all high school teachers in Air Kumbang subdistrict of Banyuasin district totaling 85 people. The sampling technique used was saturation. The research sample was 85 high school teachers. The results showed 1) there was a positive and significant effect of leadership style on teachers’ performance; 2) there was a positive and significant influence of work motivation on teachers’ performance; 3) there was a significant influence simultaneously of leadership style and work motivation on the performance of high school teachers in Air Kumbang sub-district Banyuasin.